2018
DOI: 10.1136/tsaco-2017-000152
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a randomized trial of the effect of timing of cholecystectomy during initial admission for predicted mild gallstone pancreatitis at a safety-net hospital

Abstract: BackgroundThere is evidence-based consensus for laparoscopic cholecystectomy during index admission for predicted mild gallstone pancreatitis, defined by the absence of organ failure and of local or systemic complications. However, the optimal timing for surgery within that admission is controversial. Early cholecystectomy may shorten hospital length of stay (LOS) and increase patient satisfaction. Alternatively, it may increase operative difficulty and complications resulting in readmissions.MethodsThis trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Third, some of the research data were obtained using a formula. A large-scale RCT is currently in progress [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, some of the research data were obtained using a formula. A large-scale RCT is currently in progress [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…TG18 advocates definitive surgical intervention (usually laparoscopic cholecystectomy) on the index admission in patients with acute cholecystitis or biliary pancreatitis, citing both prospective longitudinal studies and retrospective observational studies that demonstrated a significantly lower incidence of disease recurrence, hospital readmission, and overall disease-specific complications when the procedure was performed within 7 days of the onset of symptoms in the appropriate patient (recommending within 72 h as preferable) 5,17,[23][24][25][26][27][28][29][30] . However, 15 (60 per cent) of the 25 centres in the present study estimated that less than half of their patients routinely had index admission cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A protocol change occurred in August 2017 which specified a 12-hour observational period between patient enrollment and randomization to ensure that there was no evidence of clinical deterioration from mild to more severe pancreatitis. 10 This change was prompted by two patients who were initially thought to have mild gallstone pancreatitis, but progressed to severe pancreatitis requiring intensive care within the first 12 hours of hospitalization. Neither patient received cholecystectomy prior to clinical deterioration.…”
Section: Introductionmentioning
confidence: 99%